School-Based Management Level of Practice in Selected Public Elementary Schools in Mimaropa Region, Philippines (Journal of Pedagogical Inventions and Practices, 2022)
The study aimed to find out the level of practice of School-Based Management Framework in selected public elementary schools in the seven schools’ divisions of DepEd MIMAROPA region. Descriptive - correlational comparative research design using survey method was used in this study. While statistical tools such as frequency, percentages, mean, t-test and Pearson Product Moment Correlation Test were employed. Two hundred thirty-five respondents composed of 26 Public Schools District Supervisors and 209 School Heads from 375 public elementary schools from the seven schools divisions of DepEd MIMAROPA (Mindoro, Marinduque, Romblon and Palawan) region were the respondents of the study. Furthermore, all evidence of School-Based Management (SBM) principles such as Leadership and Governance, Curriculum and Learning, Accountability and Continuous Improvement and Management of Resources were described as maturing structures and mechanisms are in place to demonstrate ACCESs. Significant relationship between the school’s profile except for Sources of funds, geographical location and the level of practice of School-Based Management in terms of Leadership and Governance, Curriculum and Learning.